Psychiatric co-morbidities and substance abuse are dominant factors in Predicting Emergency Department usage rates - Lydia Mitchell; Emily Moseley; Ralph O'Neil; Lawrence M Lewis (Archives of Community Medicine and Public Health - Peertechz Publications, 2022)
Importance: 1% of the United States population accounts for 20% of healthcare costs. What characterizes heavy users of the Emergency Department (UED) both demographically and clinically is an area of active research. Objective: Compare the proportion of nine common co-morbidities between heavy, moderate, and infrequent users then compare episodic and continuous heavy UED.  Setting: A large metropolitan healthcare system. Participants: Heavy users were selected using a retrospective chart review of Barnes-Jewish Emergency Department records from 2010-2011. Emergency department usage for all unique patients seen in the time period specified was determined for two non-overlapping 365-day periods. Patients were stratified into 1 of 3 groups: Heavy users (> 10 visits for both periods), moderate users (5-9 visits for both periods), and infrequent users (1 visit in either the first or last period). There were 546 moderate users and 59,957 infrequent users matched 1:1 against 160 heavy users. These patients were matched for age, race, gender, and insurance. The 160 continuous heavy users were also compared to 388 patients who had > 10 visits in the first period, but not the second period, and 443 patients who had > 10 visits in the second period, but not the first. The proportion of subjects within each group was compared based on nine co-morbidities (substance abuse, mental illness, chronic pain, heart disease, lung disease, kidney disease, liver disease, cancer and stroke) using 95% confidence intervals. Results: Infrequent users had lower rates of all co-morbidities. Moderate users had similar rates of all co-morbidities to heavy users, except slightly higher CVA rates (13.7% v 10.6%; p = 0.49), lower rates for mental illness (33.3% v 43.1%; p = 0.08) and significantly lower rates for substance abuse (17% v 35%; p < 0.001). Only substance abuse demonstrated a significant difference between episodic and continuous heavy UED (35% v 23.5%; p = 0.002).  Conclusion: Among nine common co-morbidities, only substance abuse rates were significantly higher among heavy users compared to matched moderate UED in our healthcare system. Infrequent users had lower rates of all co-morbidities. When comparing continuous and episodic heavy emergency department users, only substance abuse rates were significantly higher.